2016
DOI: 10.2217/fon.15.303
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Utility of Single Nucleotide Polymorphisms to Guide Colorectal Cancer Screening

Abstract: Aim:To determine whether single nucleotide polymorphisms (SNPs) can be used to identify people who should be screened for colorectal cancer. Methods: We simulated one million people with and without colorectal cancer based on published SNP allele frequencies and strengths of colorectal cancer association. We estimated 5-year risks of colorectal cancer by number of risk alleles. Results: We identified 45 SNPs with an average 1.14-fold increase colorectal cancer risk per allele (range: 1.05-1.53). The colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 41 publications
1
58
0
1
Order By: Relevance
“…For example, the current 45 independent susceptibility SNPs explain 22% of familial aggregation (20). It is likely this proportion will increase as larger studies are conducted, such as the OncoArray initiative, and as more informative statistical strategies are used to devise risk-prediction SNP-based scores other than the current highly conservative paradigm of considering each SNP individually and applying stringent penalties for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the current 45 independent susceptibility SNPs explain 22% of familial aggregation (20). It is likely this proportion will increase as larger studies are conducted, such as the OncoArray initiative, and as more informative statistical strategies are used to devise risk-prediction SNP-based scores other than the current highly conservative paradigm of considering each SNP individually and applying stringent penalties for multiple testing.…”
Section: Discussionmentioning
confidence: 99%
“…To help mitigate this weakness, we used estimates based on the largest studies available, and all used data from the same source, the Colon Cancer Family Registry (26, 3234). Future studies should focus on incorporating the explicit effects of other colorectal cancer susceptibility genes such as STK11 (54) BMPR1A (55), SMAD4, PTEN (56), POLE and POLD1 (57) as well as the explicit effects of identified common low risk alleles(20). In addition to colorectal cancer risk, it is known that MMR gene mutations increase the risks of other cancers such as endometrial and ovarian cancer (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review identified 52 colorectal cancer prediction models3 with less than a third having reasonable ability to discriminate colorectal cases from those without colorectal cancer. This review and recent research has suggested utility of incorporating genetic factors in risk models including common variants such as single nucleotide polymorphisms (SNPs) 4. The second goal is development of risk tools to be simple to apply so that data on the at-risk person can be entered quickly and accurately.…”
Section: Commentarymentioning
confidence: 99%
“…They mostly employed an equation first proposed by Cox et al . in 2007, or slight modifications thereof that includes two major components: The relative risk attributable to a given SNP, commonly denoted as λ*=ppr2+qr12+qpr1+q2()p2r2+2italicpqr1+q22, where p is the population frequency of the minor allele, q = 1−p , and r 1 and r 2 are the relative risks for heterozygotes and rare homozygotes relative to common homozygotes, and the overall familial relative risk estimated from epidemiological studies, commonly denoted as λ o . The share of the familial risk attributable to the SNP is then obtained as log λ * / λ o .…”
Section: Introductionmentioning
confidence: 99%